Inversion of uterus due to prolapsed submucous fundal fibroid - Pandey, Manju; Shrestha, Binuma; Acharya, Bijay Chandra; Subedi, Hemnath; Baniya, Sebina (Nepal Journal of Obstetrics and Gynaecology, 2022)
Inversion of uterus is rarely encountered by gynecologist during practice; inversion in a non- pregnant uterus is further rarer; only case reports are published in literature on non-puerperal uterine inversion. We present a case of a 40-years multipara who had a history of irregular and excessive vaginal bleeding associated with severe lower abdominal pain during vaginal bleeding for two years. She was referred from general hospital with suspicion of cervical cancer. Being a rare clinical condition diagnosis and management of uterine inversion is challenging. High index of clinical suspicion is necessary which can be aided by radiographic imaging. Our case was diagnosed as a case of complete uterine inversion secondary to fundal fibroid clinically. She underwent abdominal hysterectomy with bilateral salpingectomy with bilateral sacrospinous vault suspension after resuscitation with fluids, blood transfusion and broad-spectrum antibiotics.